THE EFFECT OF GAMES ON VOCABULARY RETENTION - Shabaneh, Yasmin; Farrah, Mohammed (Universitas Kuningan, 2019)
Learning English has become a necessity during this century. Consequently, it is utilized in different institutions in Palestine such as schools, universities, hospitals, etc. Therefore, it is taught in schools by using different methods. Thus, in order to comprehend the language efficiently, it has to be taught in creative and interesting methods and using games inside the classroom in one of these methods. The study aims to figure out the efficiency of using games inside classrooms and to answer the research questions. The study was conducted during the first semester of 2018/2019, in which 20 participants were enrolled. The researchers collected data using pretest; posttest and class observation. The study continued for two months. In that, students were introduced to unfamiliar vocabulary through games. The findings of the research revealed the efficiency of utilizing games in the educational process. Accordingly, games help students to retain unfamiliar vocabulary, to associate new information with their surroundings and to develop their language and communicative skills.